A alfabetização científica na educação brasileira: desafios e perspectivas - Mendes, Clayton Silva (2022)
The Science, Technology and Innovation are recognized as key factors in the economic and social development of nations and are part of the economic agenda of many countries. Deepening knowledge about Science, Technology and Society is an interdisciplinary objective shared by different areas of knowledge. Training for the practice of science and for technological innovation is complex, insofar as it cannot be considered independently of the situation of basic education in Brazil, that is, of primary and secondary education. Linked to the school space, science and technology have provided numerous transformations in society. Scientific Initiation is the space where a young person's first contacts with research take place. In this sense, the research proposed here intends to identify the advantages and challenges of scientific literacy in basic education. Through five articles, it was possible to describe the types of research, funding, grants and the importance of scientific education for the training of future researchers.